Asian corporate credibility index based on Malaysian indians perceptions - Karunya, Suppayah. (Universiti Malaysia Sarawak, UNIMAS, 2009)
This study assesses how Indians in Malaysia perceive corporate credibility. It evaluates if the consumers’ perception toward the established dimension with the proposed dimension has significant effects. This paper also describes the validity and the reliability of the new dimensions as well as the previous ones that measure corporate credibility of consumers of different background that is Indians. Apart from that, this study brings about from the startingor from the developing stage of the scale to the end which shows how reliable the constructs are by using 43 items which, are described detailing the development and validation of the scale to four dimensions. The previous scale was retested and thus coming up with four valid dimensions such as corporate values/ customer oriented,expertise,reputation/image and lastly employee focus. The findings suggest that the perception of corporate credibility by Indians rely heavily on one factor and less for others.